Rasmussen encephalitis: A case report - Gupta, Rimzim; Bhargava, Rashi; Gupta, Rajesh Kumar; Gupta, Prem Prakash (Indian Journal of Child Health, 2015)
Rasmussen’s encephalitis (RE) is a chronic focal encephalitis involving single cerebral hemisphere characterized by progressive neurological dysfunction and intractable seizures. The cause is mostly unknown but proposed to be associated with immune-mediated and associated with viral infections. We report a case of RE following exanthematous illness clinically diagnosed as chickenpox.